Handbook of nucleating agents - Wypych, George (ChemTec Publishing, 2021)
"Handbook of Nucleating Agents is the most extensive monograph on the subject ever written. In addition to the Handbook, Databook of Nucleating Agents is simultaneously published to give readers comprehensive information on this important subject. The second editions of these books contain updates on new developments during the last 5 years. Handbook of Nucleating Agents gives information on how to increase the production rate, modify structure and morphology, improve mechanical performance, and reduce haze of polymeric products with proper selection of nucleating agents (and/or the so-called clarifying agents). Handbook of Nucleating Agents brings analyses of important publications found in open and patent literature. Special attention is given to the findings of the last five years which brought many new important developments."--